2018
DOI: 10.1093/ons/opy309
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of the Exposure and Surgical Freedom of the Endoscopic Extended Minipterional Craniotomy and the Transorbital Endoscopic Approach to the Anterior and Middle Cranial Fossae

Abstract: BACKGROUNDNumerous minimally invasive approaches to the skull base have been successively developed. Knowledge of the surgical nuances of a specific approach may facilitate approach selection. This study sought to compare the nuances of an extended version of the minipterional craniotomy (EMPT) with those of the transorbital endoscopic approach (TOEA) to the anterior and middle cranial fossae (ACF and MCF, respectively).OBJECTIVETo quantitatively analyze and compare the area of exposure and surgical freedom be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 24 publications
0
29
0
Order By: Relevance
“…The technique of eTOA has already been described in detail in the previous literature. 4,[10][11][12] Briefly, under general anesthesia, the patient was placed in the supine position with either a slight flexion of the head or the head in the neutral position. A skin incision was made along the superior eyelid crease after the induction of local anesthesia.…”
Section: Surgical Techniquementioning
confidence: 99%
“…The technique of eTOA has already been described in detail in the previous literature. 4,[10][11][12] Briefly, under general anesthesia, the patient was placed in the supine position with either a slight flexion of the head or the head in the neutral position. A skin incision was made along the superior eyelid crease after the induction of local anesthesia.…”
Section: Surgical Techniquementioning
confidence: 99%
“…If needed, removal of the superior orbital wall is possible, exposing the entire ACF from the midline to its most lateral point. Suchlike, the removal of the lateral orbital wall may help for an adequate view of MCF, from the lateral wall of the cavernous sinus to the lateral aspect of the temporal lobe [51].…”
Section: Discussionmentioning
confidence: 99%
“…This may also result in cardiac arrhythmias, thus, frequent monitoring of pupil size and blood pressure, along with electrocardiography, is required [29]. Intermittent relaxation of the eyeball every 20-30 min during the procedure and keeping tissues dislocation less than 10 mm is recommended [5,48,51].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some authors have suggested that vascular lesions and aneurysms cannot be safely treated using MIAs without endoscopic assistance. 22,26,30 However, all dissections in our study were carried out using only microsurgical techniques, and adequate exposure and freedom were obtained without undue difficulty.…”
Section: Discussionmentioning
confidence: 99%